2019
DOI: 10.1177/2040622319837851
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s esophagus: novel strategies for screening and surveillance

Abstract: Barrett’s esophagus is the precursor lesion for esophageal adenocarcinoma. Screening and surveillance of Barrett’s esophagus are undertaken with the goal of earlier detection and lowering the mortality from esophageal adenocarcinoma. The widely used technique is standard esophagogastroduodenoscopy with biopsies per the Seattle protocol for screening and surveillance of Barrett’s esophagus. Surveillance intervals vary depending on the degree of dysplasia with endoscopic eradication therapy confined to patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 96 publications
0
43
0
2
Order By: Relevance
“…Estimates have suggested that BE are attributable to a large number of risk factors, such as chronic gastroesophageal reflux disease symptoms, advancing age, male gender, and tobacco use [6,7]. In recent years, scholars have paid considerable attention to the association between BE risk and abdominal obesity (AO), metabolic syndrome (MetS), insulin resistance (IR), and the microbiome [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates have suggested that BE are attributable to a large number of risk factors, such as chronic gastroesophageal reflux disease symptoms, advancing age, male gender, and tobacco use [6,7]. In recent years, scholars have paid considerable attention to the association between BE risk and abdominal obesity (AO), metabolic syndrome (MetS), insulin resistance (IR), and the microbiome [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There was little difference in the incidence rates of EAC, BE and dysplasia using alternative screening methods. Although EGD with biopsy is considered the gold standard for the diagnosis and surveillance of BE [96,97], the results from these studies may encourage increased usage of alternative methods of screening for BE and EAC. Conventional EGD uses sedation, which increases the cost of screening (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al [80] commented that although brush cytology compliments histology there is an added increased cost with no true improvement. Standard OGD is expensive and associated with a small risk of complications such as bleeding, perforation, aspiration and cardiopulmonary events [81]. Since OGD is not a suitable method for screening of large populations there exists a need for alternative, cheap, widely available, and an accurate method of screening [82].…”
Section: Screeningmentioning
confidence: 99%